The Use of Extensive Reading to Encourage Students’ Reading Ability - Diska Fatima Virgiyanti (International Journal of English Learning and Applied Linguistics (IJELAL), 2020)
This study investigates the use of extensive reading to encourage students’ reading skill as well as students’ attitude toward it. Descriptive qualitative research design was employed in this sudy. The data obtained through classroom observation, questionnaire, and interview. The participant of this study were a class of first semester students of a private university in Ponorogo. The findings showed that extensive reading is useful  in teaching reading. It is known that the students extensive reading improves their vocabulary and their reading comprehension. To monitor students’ extensive reading, the lecturer asked the students to write a reding report once a week. Therefore, group discussion also implemented in the extensive reading class to activated students’ critical thinking. Besides, the result also showed that extensive reading assist students to comprehend new terms in several fields sucha as law, economics, health, politics etc. Overall, extensive reading help students to open their mind toward current issues and also boost students’ reading ability.